The scaling factor between jump height and ground contact time in drop jumps: A linear relationship at the individual level - Boccia, G.; Serranò, S.; Bonelli, B.; La Torre, A.; Pavei, G. (The Journal of Strength and Conditioning Research, 2026)
The extent to which jump height scales with changes in ground contact time (GCT) remains unknown. Establishing this relationship would enable more accurate comparisons of rebounds with different GCTs. Currently, to reliably compare reactive strength index (RSI) values, it is necessary to consider only those with similar contact time parameters. Elite young track and field athletes performed drop jumps from a 40 cm box under 3 distinct instructional conditions: (a) trade-off strategy—minimizing GCT while maximizing jump height; (b) maximizing jump height; (c) minimizing GCT. A hierarchical linear regression model was applied, with GCT and sex (male/female) as independent variables and jump height as the dependent variable. Compared with the trade-off condition, focusing on short GCT led to a 21-millisecond reduction in GCT (p < 0.0001) but also a 5.9-cm decrease in jump height (p < 0.0001). Conversely, prioritizing jump height increased jump height by 4.8 cm (p < 0.0001) but prolonged GCT by 49 milliseconds (p < 0.0001). However, RSI remained unaffected by instructions (p = 0.567). A significant main effect of GCT on jump height was observed (ß = 0.154; p < 0.00001). The full model, incorporating random and fixed effects, accounted for 94% of the variance in jump height. At the individual level, our findings confirm a linear relationship between GCT and jump height. This relationship underscores the importance of considering the GCT-jump height trade-off when assessing drop jump performance and highlights the need for evaluations across various GCT ranges rather than relying solely on 1 jump strategy.